2018
DOI: 10.1016/j.jtcme.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Kingiodendron pinnatum , a pharmacologically effective alternative for Saraca asoca in an Ayurvedic preparation, Asokarishta

Abstract: Saraca asoca (Fabaceae) is a prime ingredient in Asokarishta, a well-known Ayurvedic preparation for gynecological ailments. Due to scarcity, adulteration or substitution of related raw drugs is a common practice in its preparation. The bark of Kingiodendron pinnatum (Roxb. ex DC.) Harms, morphologically similar to S. asoca (Asoka) is a widely used substitute. The present study aimed to evaluate the pharmacological effectiveness of K. pinnatum as an alternative for S. asoca in Asokarishta by determining the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Others also described its pharmacological action. [27][28][29] We just focus here on menorrhagia, the commoner condition, not other related gynecological conditions. Some other potential substitutes mentioned for Seeta Ashoka are too rare and hence, unviable for industry e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Others also described its pharmacological action. [27][28][29] We just focus here on menorrhagia, the commoner condition, not other related gynecological conditions. Some other potential substitutes mentioned for Seeta Ashoka are too rare and hence, unviable for industry e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some other potential substitutes mentioned for Seeta Ashoka are too rare and hence, unviable for industry e.g. Nagkesar-Mesua ferrea L. 29,6 a large, rare tree in the Western Ghats forest. Similarly, another tree found effective on mice trial is Kingiodendron pinnatum 29 is a rare tree, endemic to the Western Ghats, 6 and slow growing, so is commercially unviable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K. pinnatum is occasionally used as a substitute for Saraca asoca (Asoka), which is the prime raw material in the preparation of Asokarishta, a fermented formulation, commonly used to treat gynaecological ailments especially abnormal uterine bleeding (menorrhagia). The population of the tree is less in wild but is generally used as a substitute due to its massive size and the chance of getting a good amount of bark compared to the Asoka tree [8]. A previous study revealed the pharmacological efficacy of K. pinnatum as an alternative for S. asoca in Asokarishta by demonstrating the inhibitory effect of estrogen-induced uterus endometrial thickening in immature female rats, giving scientific validation for its use in polyherbal formulations [8].…”
Section: Introductionmentioning
confidence: 99%